PENGARUH KEPRIBADIAN INDIVIDU TERHADAP GAYA MANAJERIAL YANG DIHARAPKAN - Dita Oki Berliyanti; Isuan Citra Dewi (Universitas Trisakti, 2005)
Important to have an employee which is not only suitable in knowledge, skill and ability, but also employee that have good personality and suitable with arganization culture. As a result there are qualified person that is really good employee with vision and mission which is similar with the organization. One of the benefit is those kind of employee will be loyal to the company. There for, It is important to use this theory in selection process.